The Contextual Qur’anic Interpretation of Jihad - Nur Kumala (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
In the 20th century, Indonesia was faced with issues of right-wing extremism in thename of religion which affected the benefit of the people. Several acts of terror, thediscourse of the caliphate, returning to the sunnah, and dictation of takfiri havebecome the center of topics in our country, where the issue of